The Impact of Choice on Exercise Motivation and Physical Activity in College Students - Julia Fera Tracy; Andrea Taliaferro; Alfgeir Kristjansson (The Ohio State University Libraries, 2017)
Background:   While research suggests that college courses contribute to significant health benefits, there is limited research on the effectiveness of these courses in increasing motivation and lifetime PA habits of college students. Aim:  The purpose of this study was to investigate the impact of choice in a conceptually-based college health and wellness course on exercise motivation and physical activity of undergraduate students. Method:  Participants included undergraduate students (N = 81) enrolled in a health and wellness course at a four-year liberal arts university located in the mid-Atlantic region of the U.S. Quantitative data from the Behavioral Regulation in Exercise Questionnaire and the Leisure Time in Exercise Questionnaire were collected over three time points from two groups (choice and non-choice). Qualitative data from semistructured interviews with course instructors (N = 4) and open-ended questions were also collected. Results: There was a significant increase in intrinsic regulation F(2, 158) = 10.13, p = .00, ηp2 =.114; identified regulation F(2, 158) = 7.35, p = .001, ηp2= .085; introjected regulation F(2, 158) = 6.61, p = .002, ηp2= .077; and PA F(2, 158) = 5.63, p = .004, ηp2 = .067 over time. No significant differences were found between groups. Conclusion:  While there was no significant difference between instruction type, instructors and participants suggested that choice was the preferred method for adult learners.